Titanium dioxide multi-heterogeneous interface photoelectrode modified by cobaltosic oxide quantum dots as well as construction and application of titanium dioxide multi-heterogeneous interface photoelectrode
By loading Co3O4 quantum dots onto TiO2 photoelectrodes, a multi-heterointerface photoelectrode was constructed and combined with a PEC/PMS system. This solved the problems of narrow photoresponse range and fast recombination of photogenerated charges in TiO2, achieving efficient removal of OFL and showing good application prospects.
Patent Information
- Application Number
- CN202411867166.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-18
AI Technical Summary
Existing TiO2 photoelectrodes suffer from limited photoresponse range and rapid photogenerated electron-hole recombination processes in the field of photocatalysis, which restricts their application in water treatment.
By loading Co3O4 quantum dots onto a TiO2 photoelectrode, a pn junction is constructed to form a multi-heterointerface photoelectrode. Combined with a PEC/PMS coupling system, Co3O4 is used to activate PMS to generate free radicals for synergistic oxidation of pollutants.
It significantly improves photoelectrocatalytic ability, achieving efficient and deep oxidation removal of OFL in water, improving photogenerated charge separation efficiency, achieving 100% degradation efficiency, and having low energy consumption, making it suitable for practical applications.
Smart Images

Figure CN119595731A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photoelectrode preparation, and relates to a cobalt tetroxide quantum dot-modified titanium dioxide multi-heterogeneous interface photoelectrode and its construction and application. Background Art
[0002] Quinolone antibiotics are one of the most widely used antibiotics due to their strong antibacterial ability, good efficacy characteristics, high bioavailability and low price. Ofloxacin (OFL) is a typical quinolone antibiotic, and its presence in the environment poses a huge risk to water quality, ecosystem safety and human health. Therefore, there is an urgent need to develop a green and efficient technology for removing OFL from wastewater. The most commonly used wastewater treatment technologies are divided into physical, chemical and biological treatment methods. As an efficient water treatment technology, chemical methods can quickly oxidize and completely degrade organic pollutants. Among them, advanced oxidation processes (AOPs) can produce active free radicals with strong oxidizing properties in the reaction system, attacking organic pollutants in water under appropriate conditions. It has the advantages of high mineralization efficiency, fast oxidation reaction speed and no secondary pollution. Therefore, it is one of the most studied water treatment methods in recent years. Among them, the photocatalytic technology (PC) and photoelectrocatalytic technology (PEC) of AOPs have been widely used for pollutant removal. Compared with photocatalytic technology, photoelectrocatalytic technology is spatially independent and has high electron utilization rate. It is a pollution control technology with more development prospects. However, it has the problems of non-selectivity of the main active species OH, short life span and susceptibility to environmental influences.
[0003] Semiconductor photocatalysts represented by TiO2 have the advantages of high activity, low cost, stable physical and chemical properties, and non-toxicity. They are often used to degrade organic pollutants. However, TiO2 has low electron transfer efficiency and fast electron-hole recombination rate, which limits its large-scale application.
[0004] In the past decade, people often use structural engineering and interface engineering to accelerate the charge transfer of TiO2 and reduce the electron-hole recombination rate, such as metal / non-metal doping, defect structure, noble metal modification and semiconductor coupling. For example, patent CN202110178404.X discloses a titanium dioxide photoelectrode with three-dimensional crystal face junction properties and its preparation and application. The preparation process of the photoelectrode is as follows: titanium mesh is used as a titanium source, hydrochloric acid is used as a morphology control agent, and hydrogen peroxide is used as an oxidant. A one-dimensional upright rutile TiO2 nanorod with the top {111} crystal face exposed is grown in situ on a titanium mesh substrate by a gas phase hydrothermal method; then, {101} and {111} nanosheets are grown outside the nanorods by secondary hydrothermal treatment to form a three-dimensional crystal face junction structure, which is the FH-{111}TiO2 / Ti target electrode. The patented electrode has high photoelectrocatalytic degradation performance, but TiO2 itself is still limited by the problem of limited light response range. Summary of the invention
[0005] The purpose of the present invention is to provide a cobalt tetroxide quantum dot-modified titanium dioxide multi-heterointerface photoelectrode and its construction and application, which can significantly improve the photoelectrocatalytic ability and achieve efficient deep oxidation removal of OFL in water.
[0006] The present invention has found through research that SO4 produced by advanced oxidation technology based on peroxymonosulfate (PMS) activation ·- It has the advantages of strong oxidation, long life, and wide pH range, and can efficiently degrade organic pollutants. Among the many activation methods of PMS, the activation method using solar energy to provide photogenerated electrons has the advantages of being continuous, stable, and efficient. Therefore, by constructing a PEC / PMS coupling system, while the PEC anodic oxidation of pollutants, the cathode electrons can be used to activate PMS, thereby generating a large number of free radicals to cooperate in the deep oxidation of OFL. However, there are few reports on the use of PEC / PMS coupling technology to remove pollutants.
[0007] For photoelectrocatalytic systems, light absorption, charge separation, and interfacial charge injection efficiency are the key to establishing an efficient photoelectrocatalytic active interface. At present, TiO2 semiconductor materials are the most widely used photoelectrode materials due to their low cost, non-toxicity, and good chemical stability. However, they still face the problems of narrow light absorption range and photogenerated electron-hole recombination process being much faster than surface transfer and capture process, which is not conducive to the sustainable development of TiO2 in the field of water treatment. For PMS activation materials, Co3O4 has been widely studied due to its excellent PMS activation activity. In addition, Co3O4 is a narrow bandgap (≈2.1eV) semiconductor, which has a quantum confinement effect when it exists in the form of quantum dots. Therefore, the composite of Co3O4 quantum dots (Co3O4QDs) with TiO2 is expected to improve the photoelectric performance of TiO2 photoelectrodes.
[0008] The purpose of the present invention can be achieved by the following technical solutions:
[0009] In the first aspect, the present invention provides a titanium dioxide multi-heterointerface photoelectrode modified with cobalt tetroxide quantum dots, comprising 3D TiO2 as a substrate electrode, and Co3O4 quantum dots loaded on the 3D TiO2, wherein the 3D TiO2 has an anatase-rutile "phase junction" composed of one-dimensional nanorods of rutile phase and two-dimensional anatase phase, and a pn junction is formed between the Co3O4 quantum dots and the 3D TiO2.
[0010] In a second aspect, the present invention provides a method for preparing a titanium dioxide multi-heterojunction photoelectrode modified with cobalt tetroxide quantum dots, comprising the following steps:
[0011] S1. Preparation of 3D TiO2 photoelectrode;
[0012] S2. Prepare an ethanol solution of cobalt acetate, then place the 3D TiO2 electrode in the mixed solution, perform a solvothermal reaction, wash and dry, and obtain a cobalt tetroxide quantum dot-modified titanium dioxide composite photoelectrode, namely, a 3DCo3O4 QDs@TiO2 photoelectrode.
[0013] Specifically, the preparation concept of the titanium dioxide multi-heterogeneous interface photoelectrode of the present invention is:
[0014] First, with titanium mesh as substrate, hydrochloric acid as capping agent, and hydrogen peroxide as oxidant, 1D rutile TiO2 nanorods were grown in situ on the titanium mesh by gas phase hydrothermal method, and then 2D anatase TiO2 nanosheets were covered on the nanorods by electrodeposition to obtain 3D TiO2. Finally, Co3O4 quantum dots were loaded by a simple solvothermal method to obtain Co3O4 QDs-modified TiO2 multi-heterogeneous interface photoelectrode (3D Co3O4 QDs@TiO2), which is the target product.
[0015] Furthermore, in S1, the preparation process of the 3D TiO2 photoelectrode comprises the following steps:
[0016] (1) A metal titanium mesh is used as a substrate, placed in a mixed solution of hydrochloric acid, hydrogen peroxide and water, and subjected to a gas phase hydrothermal reaction to obtain 1D rutile TiO2 nanorods in situ grown on the mesh substrate;
[0017] (2) adding hydrofluoric acid dropwise to tetrabutyl titanate, stirring evenly, transferring the mixture to a reactor for hydrothermal reaction, centrifuging, washing, and drying to obtain anatase TiO2 nanosheets;
[0018] (3) A Pt sheet and a 1D rutile TiO2 nanorod are used as the anode and cathode of a two-electrode system connected to a DC power supply, respectively. An acetone solution is used as an electrodeposition solvent. Iodine is added to improve the conductivity. A 2D TiO2 nanosheet is added to the electrodeposition solution. A fixed voltage is applied under a DC power supply for electrodeposition. After the deposition is completed, a heat treatment is performed in an air atmosphere to obtain a 3D TiO2 photoelectrode.
[0019] Furthermore, in step (1), the volume ratio of hydrochloric acid, hydrogen peroxide and water is (4.2-5.3):1:17, the mass fraction of hydrochloric acid is 36-38%, and the mass fraction of hydrogen peroxide is 30%.
[0020] Furthermore, in step (2), the volume ratio of hydrofluoric acid to tetrabutyl titanate is (3-4):25, preferably 3.5:25, and the mass fraction of the hydrofluoric acid is 35-45%.
[0021] Furthermore, in step (2), the temperature of the hydrothermal reaction is 160-200° C., preferably 180° C., and the time is 4-6 h, preferably 5 h.
[0022] Furthermore, in step (3), the ratio of the added amounts of 2D TiO2 nanosheets, elemental iodine and acetone is (18-22) mg: (18-22) mg: 50 mL, preferably 20 mg: 20 mg: 50 mL.
[0023] Furthermore, in step (3), the voltage applied during the electrodeposition process is 12 to 18 V, preferably 15 V, and the electrodeposition time is 30 to 50 min, preferably 40 min.
[0024] Furthermore, in step (3), the heat treatment temperature is 400-500°C, preferably 450°C, and the time is 1-3h, preferably 2h.
[0025] Furthermore, in S2, the concentration of the cobalt acetate ethanol solution is 0.01-0.5 mM, and can be selected as 0.01, 0.1, 0.25, 0.5 mM, etc., or any other point value within this range.
[0026] Furthermore, in S2, the temperature of the solvothermal reaction is 140-160°C, preferably 150°C, and the time is 3-5h, preferably 4h.
[0027] In the third aspect, the present invention provides an application of a titanium dioxide multi-heterointerface photoelectrode modified with cobalt tetroxide quantum dots, characterized in that a three-electrode system is constructed with 3D Co3O4 QDs@TiO2 photoelectrode as a photoanode, a Pt sheet as a cathode, and a saturated calomel electrode as a reference electrode, and a water body to be treated containing OFL, potassium permonosulfate and Na2SO4 is used as simulated wastewater. Under the irradiation of a light source, a bias voltage is applied, and photoelectrocatalysis synergistically removes ofloxacin in the water body to be treated.
[0028] Furthermore, the concentration of OFL is 2-20 mg / L, the concentration of potassium permonosulfate is 0.25-2 mol / L, and the concentration of sodium sulfate is 0.025-0.2 mol / L.
[0029] Furthermore, the light intensity of the light source is 200-600 mW / cm 2 , the applied bias voltage is +0.2~1.0V, and the degradation time is 3~20min.
[0030] The present invention has found through research that for the photoelectrocatalytic system, light absorption, charge separation and interfacial charge injection efficiency are the key to establishing an efficient photoelectrocatalytic active interface. For the activation material of PMS, transition metal catalysts represented by cobalt have attracted much attention due to their low energy demand and high efficiency. Based on this, the present invention forms a three-dimensional TiO2 structure with a "rutile-anatase" phase junction by assembling two-dimensional anatase TiO2 nanosheets with highly exposed {001} crystal planes on one-dimensional upright rutile TiO2 nanorods, and further loads Co3O4 QDs on TiO2 to construct a "Co3O4-TiO2" pn heterojunction, thereby obtaining a Co3O4 QDs@TiO2 photoelectrode material with multiple heterojunctions. The photogenerated charges are first transferred on the heterojunction through the pn heterojunction between Co3O4 and TiO2, and then separated again in the phase junction inside TiO2, which further promotes the separation and transfer of photogenerated charge carriers. This Co3O4 QDs@TiO2 photoelectrode has efficient and stable catalytic oxidation performance in the PEC / PMS coupling system, and the OFL removal rate reaches 100% within 15 minutes.
[0031] The present invention limits the amount of raw materials added (such as 2D TiO2, cobalt acetate, etc.), reaction temperature and reaction time during the preparation of the photoelectrode. First, in the preparation of the 1D TiO2 photoelectrode, the amount of hydrochloric acid and hydrogen peroxide used in the gas phase hydrothermal process and the hydrothermal time are limited. Hydrochloric acid, as a capping agent, affects the exposure of the highly reactive {111} crystal plane, hydrogen peroxide, as an oxidant, affects the size of titanium dioxide nanorods, and the reaction time affects the growth order of the nanorods.
[0032] Secondly, during the electrodeposition process, the amount of 2D TiO2 is limited. The amount of 2D TiO2 will affect the growth density of two-dimensional nanosheets. Too sparse growth is not conducive to the formation of a multi-level structure, and too dense growth is not conducive to the electron conduction between 2DTiO2 and the substrate 1DTiO2. Therefore, in the preparation process of 3D TiO2 photoelectrode, the volume ratio of hydrochloric acid, hydrogen peroxide and water during gas phase hydrothermal treatment meets 4.2:1:17~5.3:1:17, and the gas phase hydrothermal time and temperature are preferably 5h and 200℃; during electrodeposition, the amount of 2DTiO2 meets 10~40mg, and the electrodeposition time is preferably 40min to obtain a 3D TiO2 photoelectrode with the best multi-level structure.
[0033] Finally, Co3O4 quantum dots were loaded onto the surface of 3D TiO2 by solvothermal method, and the concentration of cobalt acetate, hydrothermal time and temperature were limited: (1) The concentration of cobalt acetate affects the size and loading of Co3O4 quantum dots. When the precursor concentration is too low, the loading of Co3O4 is low, and the light absorption efficiency and activation effect on PMS are not significantly improved. When the precursor concentration is too high, the loading of Co3O4 is high, the crystal plane of 3D TiO2 is blocked, affecting the multi-level structure, thereby affecting the electron transfer and limiting the photoelectrocatalytic oxidation degradation efficiency. After optimizing the concentration of the precursor, 0.03mM was determined to be the optimal concentration; (2) The hydrothermal time is too short or the temperature is too low, the loading of Co3O4 quantum dots is too low, affecting the light absorption efficiency of the photoelectrode. When the hydrothermal time is too long or the temperature is too high, the three-dimensional configuration of 3D TiO2 is affected, the interfacial activity is reduced, and the photoelectrocatalytic performance is reduced. After optimizing the hydrothermal time, 4h and 150℃ were determined to be the optimal hydrothermal time and temperature.
[0034] Compared with the prior art, the present invention has the following advantages:
[0035] (1) The substrate electrode 3D TiO2 has an advanced configuration consisting of one-dimensional nanorods and two-dimensional nanosheets. Among them, the one-dimensional upright nanorod array grown in situ on the three-dimensional mesh substrate has good electron transport properties and enhanced light absorption and scattering properties; the two-dimensional {001} TiO2 nanosheets covered by electrodeposition have a large specific surface area, which is conducive to the full exposure of active sites. In addition, the anatase phase nanosheets can also form anatase-rutile "phase junction" with the rutile phase nanorods, which is conducive to the separation and migration of photogenerated charges.
[0036] (2) Co3O4 loaded on the surface of 3D TiO2 has a narrow band gap (≈2.1 eV) and quantum confinement effect of quantum dots, which helps to improve the photoelectric performance of TiO2 photoelectrode. The formed Co3O4 / TiO2 "pn junction" cooperates with the anatase-rutile "phase junction", so that the photogenerated charge first migrates on the heterogeneous interface through the pn junction between Co3O4 and TiO2, and then separates again at the phase junction inside the titanium dioxide, further promoting the separation and transfer of photogenerated carriers. In addition, Co3O4 can efficiently activate PMS through the redox cycle of Co(III) / Co(II). Moreover, Co3O4 exists in the form of quantum dots, avoiding the occlusion of the crystal surface. Its large specific surface area fully exposes the active sites, which is conducive to the electron transfer of Co to PMS.
[0037] (3) The 3D Co3O4 QDs@TiO2 photoelectrode prepared by the present invention has good stability and practical application prospects in removing ofloxacin from water. In ordinary photocatalytic systems, the photogenerated electrons and holes are all on the photocatalyst. The photoelectrocatalytic application in the present invention transfers electrons by applying an external bias, and utilizes the multi-heterogeneous interface on the 3D Co3O4 QDs@TiO2 material to quickly separate and transfer the photogenerated electrons to the cathode, effectively improving the separation efficiency and utilization efficiency of the photogenerated charges. In addition, the PEC / PMS coupling system constructed by the present invention, while the PEC anode oxidizes the pollutants, utilizes the cathode electrons and the redox cycle of Co(III) / Co(II) to activate PMS, further promoting the separation of photogenerated charges, and generating a large number of free radicals to cooperate in the deep oxidation of OFL. After 5 cycles, the removal rate of ofloxacin was still maintained at 97.6%, the external bias was small, the electrical energy consumption was low, and it was conducive to practical application. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 The scanning electron microscope and transmission electron microscope images of 3D Co3O4 QDs@TiO2 prepared in Example 1;
[0039] Figure 2 A comparison of the photoelectric performance of 3D Co3O4 QDs@TiO2 and 3D TiO2 with different precursor concentrations prepared in Example 1;
[0040] Figure 3 The fluorescence spectra and time-resolved transient fluorescence spectra of the 3D Co3O4 QDs@TiO2 and 3D TiO2 photoelectrode prepared in Example 1;
[0041] Figure 4 Schematic diagram of the migration path of photogenerated carriers on the 3D Co3O4 QDs@TiO2 photoelectrode prepared in Example 1;
[0042] Figure 5 This is a comparison chart of the photoelectric performance of 3D CQDs@TiO2 prepared in Comparative Example 4 and 3D Co3O4 QDs@TiO2 prepared in Example 1;
[0043] Figure 6 The removal efficiency of OFL in PEC and PEC / PMS systems and the corresponding kinetic fitting curves are shown using 3D Co3O4 QDs@TiO2 and TiO2 prepared in Example 1 as photoanodes, respectively;
[0044] Figure 7 The 3D Co3O4 QDs@TiO2 prepared in Example 1 was used as a photoanode, and the removal efficiency of OFL in simulated wastewater containing different concentrations of PMS and the corresponding kinetic fitting curve;
[0045] Figure 8 The 3D Co3O4 QDs@TiO2 prepared in Example 1 was used as a photoanode, and the removal efficiency of OFL in simulated wastewater containing different concentrations of NaSO4 and the corresponding kinetic fitting curve;
[0046] Fig. 9 The 3D Co3O4 QDs@TiO2 prepared in Example 1 was used as the photoanode, and the removal efficiency of OFL and the corresponding kinetic fitting curves were applied at different bias voltages during the degradation process. DETAILED DESCRIPTION
[0047] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0048] In the following examples, unless otherwise specified, raw materials or processing techniques are conventional commercial products or conventional processing techniques in the art.
[0049] Example 1
[0050] A cobalt tetroxide quantum dot-modified titanium dioxide multi-heterogeneous interface photoelectrode and its construction and application, specifically comprising the following steps:
[0051] (1) Chemical polishing pretreatment: The metal Ti mesh was folded into a double layer and cut into a size of 3 cm × 5 cm. It was pretreated by soaking it in a chemical polishing solution (volume ratio: HNO3:HF:H2O=25:5:1) for 30 s. It was then ultrasonically cleaned in water and ethanol for 3 to 5 min respectively and then soaked in ethanol for later use.
[0052] (2) Gas-phase hydrothermal reaction: 5 mL of deionized water, 300 μL of hydrogen peroxide (30 wt%), and 1.0 mL of hydrochloric acid (37.0 wt%) were added to a 100 mL polytetrafluoroethylene-based reactor liner. The pretreated dry titanium mesh was placed on a ring-shaped bracket in the liner. The liner was placed in a high-pressure reactor and subjected to gas-phase hydrothermal reaction at 200 °C for 5 h. After the reaction was completed, the reactor was cooled to room temperature, the surface was rinsed with deionized water, and the reactor was allowed to dry naturally.
[0053] (3) Hydrothermal reaction: First, 3.5 mL of hydrofluoric acid (40% by mass) was slowly dripped into 25 mL of tetrabutyl titanate, and stirred with a magnetic stirrer during the dripping process. In the second step, the stirred solution was transferred to the polytetrafluoroethylene liner of the hydrothermal reactor (100 mL), sealed and placed in an oven for hydrothermal reaction at 180°C for 24 hours. After the reaction was completed, it was naturally cooled to room temperature, and then the obtained product was collected by centrifugation, washed with deionized water and ethanol for more than three times, respectively, to wash away the residual organic matter and other impurities, and finally the sample was placed in a vacuum drying oven and dried at 80°C for 12 hours to obtain TiO2 nanosheets for use.
[0054] (4) Electrodeposition: The Pt sheet and the electrode obtained in step (2) were used as the anode and cathode, respectively. 20 mg of the nanosheet obtained in step (3) and 20 mg of iodine were weighed and added to 50 mL of acetone solution, and ultrasonically dispersed to form the electrodeposition solution. The DC power supply was adjusted to constant voltage mode, the applied voltage was fixed at 15 V, and the deposition time was 40 min.
[0055] (5) Calcination: Calcination was carried out in air atmosphere at a temperature of 450°C, a heating rate of 3°C / min, and a calcination time of 2 h to obtain a 3D TiO2 photoelectrode.
[0056] (6) Solvothermal: Prepare a 0.03 mM ethanol solution of cobalt acetate, then place the 3D TiO2 photoelectrode obtained in step (5) in 30 mL of the above solution, perform a solvothermal reaction at 150 °C for 4 h, wash and dry to obtain a cobalt tetroxide quantum dot-modified titanium dioxide composite photoelectrode, i.e., a 3D Co3O4 QDs@TiO2 photoelectrode.
[0057] (7) The 3D Co3O4 QDs@TiO2 photoelectrode prepared above was used to remove the simulated wastewater containing ofloxacin. The specific process is as follows:
[0058] The photoelectrocatalytic experiment was carried out in a 50 mL quartz degradation cell. A three-electrode system was used to construct a PEC / PMS system based on 3D Co3O4QDs@TiO2. The distance between the working electrode and the light source was 20 cm, and the effective photoelectrode area was 2.5 × 3 cm. 2 The simulated wastewater was a mixed solution of 0.1M sodium sulfate, 20ppm OFL and 1M PMS, with a volume of 45mL. The light source was a 300W xenon lamp with a light intensity of 520mW / cm 2 The bias voltage was +0.4 V (relative to saturated calomel electrode) and the photoelectrocatalytic experiment was carried out. The reaction time was 15 min, and samples were taken at regular intervals. The OFL concentration in the samples was tested by Agilent 1260 high performance liquid chromatography. The specific degradation results are shown in Figure 2. Figure 6As shown, (a) represents the removal curve of OFL, and (b) represents the corresponding first-order kinetic curve.
[0059] Figure 6 The test results show that, first, compared with the single PEC system, the PEC / PMS system has a higher OFL removal rate. And whether it is the PEC system or the PEC / PMS system, the OFL degradation efficiency is higher after TiO2 is loaded with Co3O4 QDs. Finally, compared with TiO2, after coupling PEC with PMS, the efficiency of Co3O4 QDs@TiO2 oxidation removal of OFL increases more (2.6 times-3.6 times). It shows that the 3D Co3O4 QDs@TiO2 photoelectrode successfully realizes the efficient photoelectrocatalytic redox of ofloxacin-containing wastewater in the PEC / PMS system.
[0060] Comparative Example 1:
[0061] Compared with Example 1, most of the contents are the same, except that in this example: the simulated wastewater in step (7) is a mixed solution of 0.1 mol / L sodium sulfate solution and 20 mg / L OFL.
[0062] Comparative Example 2:
[0063] Compared with Example 1, most of them are the same, except that in this embodiment: the working electrode in step (7) is 3DTiO2.
[0064] Comparative Example 3:
[0065] Compared with Example 1, most of the contents are the same, except that in this example: the concentrations of cobalt acetate in step (6) are 0.01 and 0.05 mM, respectively.
[0066] Comparative Example 4:
[0067] Compared with Example 1, most of the steps are the same, except that in this example: the cobalt tetroxide quantum dots in step (6) are replaced with carbon quantum dots.
[0068] Performance Testing
[0069] 1. Scanning Electron Microscope Analysis
[0070] Field emission scanning electron microscopy (Hitachi S-4800) and scanning transmission electron microscopy (JEM-2100) were used to characterize the microstructure of the electrodes. Figure 1 As shown in a, 1D TiO2 nanorods grow perpendicular to the substrate on the titanium mesh, with diameters ranging from 110nm to 220nm. The 2D TiO2 nanosheets evenly cover the gaps between the nanorods, and the loaded Co3O4 QDs can be Figure 1 It was observed in b that the diameter is about 6 nm.
[0071] 2. Photoelectrochemical performance test
[0072] The photoelectrocatalytic oxidation performance of the 3D TiO2 and 3D Co3O4 QDs@TiO2 photoelectrodes prepared in Example 1 was studied, and the specific steps were as follows:
[0073] The photoelectrocatalytic performance test was carried out in a square quartz reaction cell. The electrolyte solution was 0.1 mol / L sodium sulfate solution. A three-electrode system was used, with 3D TiO2 and 3D Co3O4 QDs@TiO2 as working electrodes, platinum as counter electrode, and saturated calomel electrode as reference electrode. The linear sweep voltammetric curve, Mott-Schottky curve, transient photocurrent response curve and AC impedance spectrum were tested using a Chenhua CHI660C electrochemical workstation. A xenon lamp was used as the light source, and the distance between the light source and the working electrode was 1 cm. The test results are shown in Figure 2. Figure 2 The results show that the photoresponse performance of 3D Co3O4 QDs@TiO2 electrode is significantly better than that of 3D TiO2, and the photocurrent density can reach 0.8 mA / cm 2 , which is 2.0 times that of 3D TiO2. The impedance value is about 466.0Ω, which is about 0.7 times smaller than that of 3D TiO2. The calculated carrier concentration is 8.9×10 28 cm -3 , which is about 25.5 times higher than that of 3D TiO2.
[0074] 3. Fluorescence spectroscopy and time-resolved transient fluorescence spectroscopy tests
[0075] The 3D TiO2 and 3D Co3O4 QDs@TiO2 photoelectrodes prepared in Example 1 were used for fluorescence spectroscopy and time-resolved transient fluorescence spectroscopy tests. Figure 3 a, Compared with the 3D TiO2 electrode, the luminescence intensity of the 3D Co3O4 QDs@TiO2 photoelectrode is much weaker, indicating that the loading of Co3O4 quantum dots significantly inhibits the recombination of photogenerated charges. Figure 3 As shown in b, the decay rate of carriers on 3D Co3O4QDs@TiO2 is slower, proving that its ability to separate photogenerated electron-hole pairs is stronger. This shows that the loading of Co3O4 quantum dots significantly improves the separation efficiency of TiO2 photogenerated charges and prolongs the lifetime of excited electrons (3D TiO2: 0.96ns; 3D Co3O4 QDs@TiO2: 72ns), allowing more holes to reach the surface to participate in the oxidation reaction, thereby improving the efficiency of oxidative degradation of pollutants.
[0076] The present invention significantly improves the photoelectric performance by introducing Co3O4 quantum dots, and solves the problems of narrow light absorption range and fast recombination rate of photogenerated charges in traditional TiO2 materials. Figure 5 It is shown that when Co3O4 quantum dots are changed to carbon quantum dots (CQDs), the photoelectric performance of the material decreases significantly, showing the unique properties and advantages of Co3O4 quantum dots. At the same time, Co3O4 shows excellent effects in PMS activation, can efficiently activate PMS, and significantly enhance the pollutant removal ability. In addition, the PEC / PMS coupling system constructed by the present invention utilizes cathode electrons and the redox cycle of Co(III) / Co(II) to activate PMS while the pollutants are oxidized at the PEC anode, thereby further promoting the separation of photogenerated charges and generating a large number of free radicals to achieve synergistic deep oxidation. During operation, the system has low energy consumption, significantly improved energy efficiency, good economy, and is suitable for sustainable development in fields such as water treatment, showing its unique application potential.
[0077] In terms of technical means, the combination of PEC and PMS can achieve the synergistic removal of pollutants by multiple free radicals. The PEC technology alone is used to remove OFL. The rest is the same as in Example 1. Comparative Example 2 of constructing a PEC system to degrade OFL is shown in the following results. Figure 6 Compared with the single PEC system, after the introduction of PMS, the oxidation efficiency of 3D TiO2 on OFL increased from 82.0% to 97.4%, and the corresponding first-order kinetic constant increased from 0.038min -1 Increase to 0.10min -1 The oxidation efficiency of OFL by 3D Co3O4 QDs@TiO2 was significantly increased from 62.3% to 100.0%, and the corresponding kinetic rate constant was also increased from 0.064min -1 Increased to 0.24min -1 , indicating that the activation of PMS promoted the oxidation process of OFL.
[0078] 3D TiO2 was used as the photoanode, and the rest was the same as in Example 1 to construct Comparative Example 2 for photoelectrocatalytic coupling of persulfate oxidation and degradation of OFL (the specific implementation process can be seen in Comparative Example 2). The results are as follows Figure 6 Compared with the PEC / PMS system with TiO2 as the photoanode, the PEC / PMS system with 3D Co3O4 QDs@TiO2 as the photoanode can increase the oxidation efficiency of OFL from 71.7% to 100.0% within 15 min, and the corresponding first-order kinetic constant increases from 0.10 min -1 Increased to 0.24min -1 This indicates that the PEC / PMS system constructed based on 3DCo3O4 QDs@TiO2 can achieve efficient removal of OFL.
[0079] Embodiment 2 to Embodiment 3
[0080] Compared with Example 1, most of the contents are the same, except that in this example: the masses of 2D TiO2 nanosheets in step (4) are 10 mg and 40 mg respectively.
[0081] Embodiment 4 to Embodiment 5
[0082] Compared with Example 1, most of the contents are the same, except that in this example: the concentrations of cobalt acetate in step (6) are 0.01 mM and 0.05 mM respectively.
[0083] Embodiment 6 to Embodiment 7
[0084] Compared with Example 1, most of the contents are the same, except that in this example: the PMS concentrations in step (7) are 0.25 mM, 0.5 mM and 2 mM, respectively.
[0085] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A cobalt tetroxide quantum dot-modified titanium dioxide multi-heterojunction photoelectrode, characterized in that: It includes 3D TiO2 as a base electrode and Co3O4 quantum dots loaded on the 3D TiO2, wherein the 3D TiO2 has an anatase-rutile "phase junction" composed of one-dimensional nanorods of a rutile phase and a two-dimensional anatase phase, and a pn junction is formed between the Co3O4 quantum dots and the 3D TiO2.
2. The method for preparing a cobalt tetroxide quantum dot-modified titanium dioxide multi-heterointerface photoelectrode according to claim 1, characterized in that: The following steps are involved: S1. Preparation of 3D TiO2 photoelectrode; S2. Prepare an ethanol solution of cobalt acetate, then place the 3D TiO2 electrode in the mixed solution, perform a solvothermal reaction, wash and dry, and obtain a cobalt tetroxide quantum dot-modified titanium dioxide composite photoelectrode, namely, a 3DCo3O4 QDs@TiO2 photoelectrode.
3. The method for preparing a cobalt tetroxide quantum dot-modified titanium dioxide multi-heterointerface photoelectrode according to claim 2, characterized in that: In S1, the preparation process of the 3D TiO2 photoelectrode comprises the following steps: (1) A metal titanium mesh is used as a substrate, placed in a mixed solution of hydrochloric acid, hydrogen peroxide and water, and subjected to a gas phase hydrothermal reaction to obtain 1D rutile TiO2 nanorods in situ grown on the mesh substrate; (2) adding hydrofluoric acid dropwise to tetrabutyl titanate, stirring evenly, transferring the mixture to a reactor for hydrothermal reaction, centrifuging, washing, and drying to obtain anatase TiO2 nanosheets; (3) A Pt sheet and a 1D rutile TiO2 nanorod are used as the anode and cathode of a two-electrode system connected to a DC power supply, respectively. An acetone solution containing 2D TiO2 nanosheets and iodine is used as the electrodeposition solution. A fixed voltage is applied under a DC power supply for electrodeposition. After the deposition is completed, heat treatment is performed in an air atmosphere to obtain a 3D TiO2 photoelectrode.
4. The method for preparing a cobalt tetroxide quantum dot-modified titanium dioxide multi-heterojunction photoelectrode according to claim 3, characterized in that: In step (1), the volume ratio of hydrochloric acid, hydrogen peroxide and water is (4.2-5.3):1:17, the mass fraction of hydrochloric acid is 36-38%, and the mass fraction of hydrogen peroxide is 30%.
5. The method for preparing a cobalt tetroxide quantum dot-modified titanium dioxide multi-heterointerface photoelectrode according to claim 3, characterized in that: In step (2), the volume ratio of hydrofluoric acid to tetrabutyl titanate is (3-4):25, and the mass fraction of the hydrofluoric acid is 35-45%; The temperature of the hydrothermal reaction is 160-200°C and the time is 4-6 hours.
6. The method for preparing a cobalt tetroxide quantum dot-modified titanium dioxide multi-heterointerface photoelectrode according to claim 3, characterized in that: In step (3), the ratio of the added amounts of 2D TiO2 nanosheets, elemental iodine and acetone is (18-22) mg: (18-22) mg: 50 mL.
7. The method for preparing a cobalt tetroxide quantum dot-modified titanium dioxide multi-heterointerface photoelectrode according to claim 3, characterized in that: In step (3), the voltage applied during the electrodeposition process is 12 to 18 V, and the electrodeposition time is 30 to 50 min; The heat treatment temperature is 400-500°C and the time is 1-3h.
8. The method for preparing a cobalt tetroxide quantum dot-modified titanium dioxide multi-heterointerface photoelectrode according to claim 2, characterized in that: In S2, the concentration of the cobalt acetate ethanol solution is 0.01-0.5 mM; The temperature of the solvent thermal reaction is 140-160°C and the time is 3-5 hours.
9. The use of the cobalt tetroxide quantum dot-modified titanium dioxide multi-heterojunction photoelectrode as claimed in claim 1, characterized in that: A three-electrode system was constructed with 3D Co3O4 QDs@TiO2 photoelectrode as the photoanode, Pt sheet as the cathode, and saturated calomel electrode as the reference electrode. The treated water containing OFL, potassium permonosulfate and Na2SO4 was used as the simulated wastewater. Under the irradiation of light source, bias voltage was applied, and photoelectrocatalysis synergistically removed ofloxacin in the treated water.
10. The use of the cobalt tetroxide quantum dot-modified titanium dioxide multi-heterojunction photoelectrode according to claim 9, characterized in that: The concentration of OFL is 2-20 mg / L, the concentration of potassium permonosulfate is 0.25-2 mol / L, and the concentration of sodium sulfate is 0.025-0.2 mol / L; Light intensity is 200~600mW / cm 2 , the applied bias voltage is +0.2~1.0V, and the degradation time is 3~20min.
Citation Information
Patent Citations
Preparation method and application of titanium dioxide heterojunction photoanode
CN103922608A
Composite photocatalytic electrode of photo-reduction metal modified cobaltosic oxide / titanium dioxide p-n heterojunction and preparation of composite photocatalytic electrode
CN106745534A
Preparation method for metal organic framework-derived tricobalt tetroxide-modified titanium dioxide nanotube array
CN108525667A
Titanium dioxide photoelectrode with three-dimensional crystal facet junction property and preparation and application thereof
CN113189174A
Methods of making metal-oxides and uses thereof for water treatment and energy applications
US20120267321A1